Successful Management of Glioblastoma Chemotherapy-Associated Dysgeusia with Gabapentin. (5th November 2020) - Turcotte, Karen; Touchette, Charles Jean; Iorio-Morin, Christian; Fortin, David
ABSTRACT: Dysgeusia is a frequent, yet underreported side effect of chemotherapy for cancer. We report here the first use of gabapentin in two glioblastoma patients who developed dysgeusia following intra-arterial administration of carboplatin or oral administration of lomustine, respectively. Treatment initiation was followed by resolution of taste alteration within weeks. Both patients reported significant improvement in their quality of life and regained weight, allowing further chemotherapy cycles. We hypothesized that in these two cases, chemotherapy impeded gustatory cells turnover and function, resulting in a gustatory "deafferentation-like" syndrome which was successfully addressed by the medication.